Effects of biodiesel blends on the kinetic and thermodynamic parameters of fossil diesel during thermal degradation. (15th October 2019) - Li, Hui; Liu, Fengsheng; Ma, Xiaoling; Cui, Ping; Gao, Yan; Yu, Mingzhi; Guo, Min
Highlights: Biodiesel concentration in biodiesel-diesel blends could be easily measured by FTIR. The average E a, n, and ΔH of B20 was similar to that of B0. Thermal degradation of biodiesel-diesel blends was endothermic and nonspontaneous. Unlike B0 and B5, evolved products of aldehyde and ether were found in B20 and B50. Abstract: To investigate the effects of biodiesel on thermal degradation for diesel, especially on its kinetic and thermodynamic parameters, three biodiesel–diesel blends, namely, B5, B20, and B50 were prepared on the basis of volume ratio and the thermal degradation was compared with that of fossil diesel. The experiments were conducted via thermogravimetry (TG) in combined with Fourier Transform infrared spectroscopy (FTIR) at linear heating rates of 5 K min −1, 10 K min −1, 15 K min −1, and 20 K min −1 with temperature range from 298 K to 873 K. In the meantime, generated products during the process were measured by FTIR in real time. Based on TG results, two model free methods of Friedman and Flynn–Wall–Ozawa were adopted to calculate the activation energy ( E a ). As for the reaction order ( n ), it was determined by Avrami theory. In addition, thermodynamic parameters of enthalpy change ( ΔH ), Gibbs free energy ( ΔG ), and entropy change ( ΔS ) during thermal degradation were also calculated and compared.